Novel and newer nucleic acid amplification tests for the diagnosis of TB - Matinyenya, Brian (Division of Pulmonology, 2016)
Background: Current tools for TB diagnosis have suboptimal accuracy, perform poorly in diagnosing extra-pulmonary TB, and are not point of care; hence results have a slow turn-around time. Objective: This project evaluated the diagnostic accuracy of the promising novel loop mediated isothermal amplification (LAMP) assay on sputum, and that of the semi-automated Xpert MTB/RIF (Xpert) test on non-sputum specimens (bronchoalveolar lavage fluid [BALF], tracheal aspirates, and cerebrospinal fluid [CSF]) from South African patients with suspected TB (the accuracy of Xpert using these fluids was unknown at the time this work was performed). Methodology: Biological samples (sputum, tracheal aspirates, BALF, or CSF) were collected from patients with suspected TB. Liquid culture served as the reference standard for the diagnosis of definite TB. Accuracy was evaluated according to HIV and smear microscopy status, where appropriate. The relationship between test performance and bacterial load (culture time-to-positivity [TTP]) was also compared. For the evaluation of LAMP, 2 spot sputa of approximately 4 ml were collected from 301 patients (60 μl of sputum was used for the assay). For the evaluation of Xpert on BALF, 152 patients who were sputum scarce or smear-negative were recruited (1 ml of the BALF aliquot or a re-suspended pellet from 10 ml BALF was used). For the evaluation of Xpert on tracheal aspirates, 120 tracheal aspirates from patients enrolled in the intensive care unit (ICU) were tested. For the evaluation of Xpert on CSF, 235 patients with suspected TBM had a lumbar puncture with 1 ml of CSF or where available a re-suspended pellet from 3 ml of CSF evaluated using Xpert.